2021
DOI: 10.1038/s41531-021-00210-w
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein-induced dysregulation of neuronal activity contributes to murine dopamine neuron vulnerability

Abstract: Pathophysiological damages and loss of function of dopamine neurons precede their demise and contribute to the early phases of Parkinson’s disease. The presence of aberrant intracellular pathological inclusions of the protein α-synuclein within ventral midbrain dopaminergic neurons is one of the cardinal features of Parkinson’s disease. We employed molecular biology, electrophysiology, and live-cell imaging to investigate how excessive α-synuclein expression alters multiple characteristics of dopaminergic neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 166 publications
(332 reference statements)
2
15
0
Order By: Relevance
“…Noteworthy, in line with the absence of other signs of degeneration, 23 the dendritic arbor of DA cells is preserved at an earlier time‐point (5‐month‐old Snca +/+ rats). Interestingly, a recent study in neuronal cultures of midbrain DA neurons also demonstrated that virally induced α‐syn–overexpressing neurons exhibit a lower degree of dendritic arborization compared with naive DA neurons 48 . Altogether, α‐syn–dependent somatodendritic alterations observed in aged Snca +/+ nigral DA neurons model the pathological changes of the DAergic system occurring in humans during PD progression 43,45‐47 and provide additional insights into the mechanisms by which α‐syn overload drives SNpc DA neurons' pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, in line with the absence of other signs of degeneration, 23 the dendritic arbor of DA cells is preserved at an earlier time‐point (5‐month‐old Snca +/+ rats). Interestingly, a recent study in neuronal cultures of midbrain DA neurons also demonstrated that virally induced α‐syn–overexpressing neurons exhibit a lower degree of dendritic arborization compared with naive DA neurons 48 . Altogether, α‐syn–dependent somatodendritic alterations observed in aged Snca +/+ nigral DA neurons model the pathological changes of the DAergic system occurring in humans during PD progression 43,45‐47 and provide additional insights into the mechanisms by which α‐syn overload drives SNpc DA neurons' pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Another important feature highlighted in the present study is the dystrophic TH + dendritic arborizations, branching from SNpc surviving DAergic neurons towards the SNpr in LPS Snca +/+ rats, anticipating by almost seven months similar alterations in the naϊve Snca +/+ animals 21 . The loss of neuronal complexity and the decreased dendritic arborization have been linked to α-synuclein overexpression in virally infected DAergic neurons in vitro and in vivo , preceding their eventual death 34,35 and resembling PD patient’s post- mortem alterations 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Our data showing dysregulation of dopamine release and genes related to dopamine synthesis suggests a possible association with α-Syn accumulation and calcium homeostasis. Overexpression of α-Syn has been shown to decrease the auto-inhibitory function of D2 receptors in DA neurons and increase intracellular and extracellular dopamine levels and tyrosine hydroxylase expression 53 . Furthermore, calcium has been shown to directly and indirectly increase α-Syn pathology [54][55][56] .…”
Section: Discussionmentioning
confidence: 99%